Iron‐responsive chromatin remodelling and MAPK signalling enhance adhesion in Candida albicans. Issue 2 (15th June 2014) - Puri, Sumant; Lai, William K. M.; Rizzo, Jason M.; Buck, Michael J.; Edgerton, Mira
Summary Recent cumulative data show that various transcription factors are recruited to the chromatin in an iron‐responsive manner to affect diverse cellular functions in the pathogenic fungus Candida albicans. Here we identified groups of iron‐responsive genes in C. albicans by chromatin remodelling analysis at gene promoters, using micrococcal nuclease (MNase) digestion followed by deep sequencing. Chromatin in the promoter regions of iron uptake and utilization genes showed repressed and active configuration, respectively, under iron‐replete conditions. GO Term enrichment analysis of genes with differentially remodelled chromatin, in respective promoter locales, suggested that many genes involved in adhesion are also iron‐responsive. C. albicans was observed to be more self‐adherent (twofold increase) and formed higher biofilm mass (77% increase) in the presence of iron. Furthermore, we identified various known and novel adhesion‐related genes with iron‐dependent active chromatin profiles that are indicative of potential upregulation under iron‐replete conditions. Transcription factor Cph1 that is activated upon Cek1 phosphorylation also showed an active chromatin profile under iron‐replete conditions and cells showed iron‐responsive Cek1 MAPK phosphorylation in the presence of iron. Thus, iron affects diverse biological functions by modulating chromatin profiles of large gene sets and by signalling through Cek1 MAPK in C. albicans.